BUKU KAS BERBASIS WEBSITE PADA USAHA KATERING DI PANTI ASUHAN PUTRI AISYIYAH MALANG - Dimas Wahyu Wibowo; Eka Larasati Amalia; mustika mentari; Ahmadi Yuli Ananta; Muhammad Shulhan Khairy; Farida Ulfa; Meuti Zari Annisa; Ivan Abdurrafie; Irsyadha Alfyrdhousi Redhysyahputra (Publisher UPT P2M Politeknik Negeri Malang, 2021)
Community Service, which becomes the main discussion in this article, shows the real role of the world of information technology in helping community service partners. Aisyiyah Putri Orphanage (PAP'A) Malang, as the community service partner, has a catering business and many customers from universities, or hospitals, as well as other communities. The growing number of PAP'A's catering business customers require special handling of the documentation of the expenditure and income, to this point, the recording of the cash book and the preparation of financial reports are still done manually on paper, books or using excel. This has the impact of data inaccuracy due to human error, difficulty in data tracing, or receipts and bills for data recap are sometimes missing and making it difficult to find detailed information about orders in PAP'A catering business. To overcome this problem, developing a website-based cash book to assist and facilitate information on the expenditure and income in PAP'A's catering business is required. Making a web-based digital cash book application can make it easier and make cash flow information and financial reports neater and easier to trace. The partner of this community service activity will benefit from increasing the quality of knowledge and mastery of human resources in the field of digitizing digital ledgers. This will be a provision for the orphanage manager to be able to make income and expenditure reports